Sensitivity of water and carbon fluxes to climate changes from 1960 to 2100 in European forest ecosystems - Davi, H.; Dufrêne, E.; François, C.; Le Maire, G.; Loustau, D.; Bosc, A.; Rambal, S.; Granier, A.; Moors, E. (Agricultural and Forest Meteorology, 2006)
The effects of climate changes on carbon and water ﬂuxes are quantiﬁed using a physiologically multi-layer, process-based model containing a carbon allocation model and coupled with a soil model (CASTANEA). The model is ﬁrst evaluated on four EUROFLUX sites using eddy covariance data, which provide estimates of carbon and water ﬂuxes at the ecosystem scale. It correctly reproduces the diurnal ﬂuxes and the seasonal pattern. Thereafter simulations were conducted on six French forest ecosystems representative of three climatic areas (oceanic, continental and Mediterranean areas) dominated by deciduous species (Fagus sylvatica, Quercus robur), coniferous species (Pinus pinaster, Pinus sylvestris) or sclerophyllous evergreen species (Quercus ilex). The model is driven by the results of a meteorological model (ARPEGE) following the B2 scenario of IPCC. From 1960 to 2100, the average temperature increases by 3.1 8C (30%) and the rainfall during summer decreases by 68 mm (27%). For all the sites, between the two periods, the simulations predict on average a gross primary production (GPP) increase of 513 g(C) m 2 (+38%). This increase is relatively steep until 2020, followed by a slowing down of the GPP rise due to an increase of the effect of water stress. Contrary to GPP, the ecosystem respiration (Reco ) raises at a constant rate (350 g(C) m 2 i.e. 31% from 1960 to 2100). The dynamics of the net ecosystem productivity (GPP minus Reco ) is the consequence of the effect on both GPP and Reco and differs per site. The ecosystems always remain carbon sinks; however the sink strength globally decreases for coniferous (8%), increases for sclerophyllous evergreen (+34%) and strongly increases for deciduous forest (+67%) that largely beneﬁts by the lengthening of the foliated period. The separately quantiﬁed effects of the main variables (temperature, length of foliated season, CO2 fertilization, drought effect), show that the magnitude of these effects depends on the species and the climatic zone
Keywords: canopy scale; carbon sink; climate change; forest ecosystems; Phenology